2006
DOI: 10.1073/pnas.0601347103
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of T cell activation and tolerance by PDL2

Abstract: T cell activation and tolerance are regulated by costimulatory molecules. Although PD-1 serves as a crucial negative regulator of T cells, the function of its ligands, PDL1 and PDL2, is still controversial. In this study, we created a PDL2-deficient mouse to characterize its function in T cell activation and tolerance. Antigenpresenting cells from PDL2؊͞؊ mice were found to be more potent in activation of T cells in vitro over the wild-type controls, which depended on PD-1. Upon immunization with chicken ovalb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(136 citation statements)
references
References 43 publications
7
128
0
Order By: Relevance
“…Our results thus agree on the roles of PD-1 and PD-L1 as negative costimulatory molecules in T1D as described by others (15)(16)(17). Interestingly, PD-L2 was recently found to be important in CD4 ϩ T cell tolerance to oral Ags (26). Impairments of an immune tolerance mechanism regulated by PD-1 could thus lead to susceptibility to autoimmunity, while inhibiting PD-1 may be explored in the boosting of immunity to infectious agents and to cancer.…”
Section: Pd-1/pd-l1 Interaction Restricts Effector Differentiation Ofsupporting
confidence: 78%
“…Our results thus agree on the roles of PD-1 and PD-L1 as negative costimulatory molecules in T1D as described by others (15)(16)(17). Interestingly, PD-L2 was recently found to be important in CD4 ϩ T cell tolerance to oral Ags (26). Impairments of an immune tolerance mechanism regulated by PD-1 could thus lead to susceptibility to autoimmunity, while inhibiting PD-1 may be explored in the boosting of immunity to infectious agents and to cancer.…”
Section: Pd-1/pd-l1 Interaction Restricts Effector Differentiation Ofsupporting
confidence: 78%
“…Although an additional effect of anergy cannot be formally excluded, these results demonstrate that the observed decline of OT-I cells activated by filterable Ag resulted to a great extent from deletion. The mechanisms inducing such tolerance remain to be identified, but may be related to the selective expression of B7-DC (PD-L2), which negatively regulates T cell activation (44,45), on DCs carrying filterable Ag. Alternative to deletion, it is possible that regulatory CD4 ϩ T cells were induced and contributed to tolerance against filterable Ag.…”
Section: Discussionmentioning
confidence: 99%
“…After 5 days, the spleens and LNs from secondary recipient mice were taken and analyzed for surviving Thy1. spleen expressed more B7-DC (PD-L2), a negative regulator of T cell activation (44,45), than other DCs (Fig. 9).…”
Section: V␤5mentioning
confidence: 99%
“…Further studies have correlated the over-expression of this gene to the negative regulation of T-cell activation. In one particular study, PDL2 (Pdcd1lg2) deficient mice were created in order to characterise the function of this gene in T-cell activation and tolerance, and results generated from this study suggested that Antigen-presenting cells from PDL2-deficient mice were found to be more potent in activating T-cells in vitro when compared to the wild-type counterparts [22]. These findings are conclusive and correlate well with the results generated from our in-house microarray experiments because using MicroPath to compare all three of our datasets followed by extracting gene expression patterns from them resulted in an important finding that Pdcd1lg2 was not only found to be over-expressed in tolerance (fold change of 3.921), but it was also under-expressed in our KOA0 Vs WTA0 and KOA6 Vs WTA6 knock-out datasets (with a fold change of 1.140 and 0.079 respectively) ( Table 2).…”
Section: Deciphering Gene Regulatory Network Of Co-xpressed Genes VImentioning
confidence: 99%